Catalogue 2.0 : the future of the library catalogue - Chambers, Sally, 1974- (Chicago : Neal-Schuman, 2013)
Without exploring the library catalogue, a user will now know which books are to be found in the library, or where they can be found. But in the last 25 years, the nature of the library catalogue has changed immensely, and cataloguing-- the essential skill of bibliographic description-- is undergoing a steady evolution. This collection of essays provides an overview of the current state, and then looks to the future to see what the library catalogue might become.
Next-generation catalogues : what do users think? / Anne Christensen -- Making search work for the library user / Till Kinstler -- Next-generation discovery : an overview of the European scene / Marshall Breeding -- The mobile library catalogue / Lukas Koster and Driek Heesakkers -- FRBRizing your catalogue : the facets of FRBR / Rosemie Callewaert -- Enabling your catalogue for the Semantic Web / Emmanuelle Bermès -- Supporting digital scholarship : bibliographic control, library co-operatives and open access repositories / Karen Calhoun -- Thirteen ways of looking at libraries, discovery and the catalogue : scale, workflow, attention / Lorcan Dempsey.
"First published in the United Kingdom by Facet Publishing, 2013"--Title page verso.
Includes bibliographical references and index.
Keywords: Online library catalogs; Electronic information resource searching; Web 2.0.; Semantic Web; Electronic information resource searching; Online library catalogs; Semantic Web; Web 2.0.